Analisis Potensi Pajak Daerah untuk Peningkatan Kapasitas Fiskal Kabupaten dan Kota di Sulawesi Utara - Ering, Sherly; Hakim, Dedi Budiman; Juanda, Bambang (UI Scholars Hub, 2016)
Despite recording double digit growth since 2005, North Sulawesi’s tax to GDRP ratio has been fairly stable at about 0,24% on average (6,89% to total revenue). This paper cataloques a range of factors that may account for the local tax potential of North Sulawesi’s to strengthen its fiscal capacity. Calculation on local tax potency especially on restaurant tax confirm gap between real revenues and its potency about Rp1.06 billion. By using panel data through econometric methodologies, the paper assesses the statistical significance of a number of potential determinants of local tax revenue, using data from 15 regions in North Sulawesi over the period 2009–2014. The results indicate that, among the variables that exert a statistically significant influence on local tax potential are per capita GDRP, agriculture sectors, and high school number, while the employee has no statistically significance.